Making smart investment decisions in clinical research. Issue 1 (December 2015) - Bansback, Nick; Keystone, Edward; O'Dell, James; Phibbs, Ciaran; Hannagan, Keri; Brophy, Mary; Anis, Aslam
Abstract A recent trial in rheumatoid arthritis found an inexpensive, but infrequently used, combination of therapies is neither inferior nor less safe than an expensive biologic drug. If the trial had been conducted over 10 years ago, arguably 100's of millions of dollars since spent on biologics could have been released to other, more effective treatments. Given the ever increasing number of trials proposed, this commentary uses the trial as an example to challenge payers and research funders to make smarter investments in clinical research to save potential future costs. Trial registration:NCT00405275, registered 29 November 2006